ANALISIS RISIKO KESEHATAN LINGKUNGAN PAPARAN SULFUR DIOKSIDA (SO2) UDARA AMBIEN PADA PEDAGANG KAKI LIMA DI TERMINAL BUS PULOGADUNG, JAKARTA TIMUR - Kunti Wijiarti; Yusniar Hanani Darundiati; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
The contribution of air pollution in urban areas around 87% comes from transportation activities. Pulogadung Bus Station in East Jakarta is one of the potential sites in pollution emissions of SO2 gas. Street vendors are the population most at risk for contamination of vehicle exhaust gases. The purpose of this research was analyze the level of non-carcinogenic health risks of exposure to SO2 against street vendors at Pulogadung Bus Station due to transportation activities. This research used observational research with approach Environmental Health Risk Assessment. The population in this research was 140 street vendors at Pulogadung Bus Station with a sample of 60 street vendors. SO2 measurements performed by pararosanilin method using a spectrophotometer. The results showed the average concentration of SO2 at Pulogadung Bus Station was 133,78 ug/m3 which means it is still well below the standards set by the Governor Decree No. 551 of 2001. The average weight of respondents 58 kg, the average daily exposure time 13 hours/day, the average frequency of exposure 329 days/year and the average duration of exposure for 15 years. The average intake of SO2 real time is 0.01461 mg/kg/day and intake life time is 0.02412 mg/kg/day. The average RQ in real time exposure is 0.5619 mg/kg/day and the life time of exposure is 0.9278 mg/kg/day. Characteristics of non-carcinogenic health risks of exposure to SO2 on street vendors at Pulogadung Bus Station in East Jakarta indicate that as many as 13 street vendors (21.67%) exposure in real time and 19 street vendors (31.67%) in the life time risk exposure resulting from exposure to SO2. The conclusion of this study is street vendors in Pulogadung Bus Station have categories yet non carcinogenic health risk by exposure to SO2.